1987
DOI: 10.1021/j100308a015
|View full text |Cite
|
Sign up to set email alerts
|

Coordination structures for uranyl carboxylate complexes in aqueous solution studied by IR and carbon-13 NMR spectra

Abstract: The interaction of uranyl ion with acetic, glycolic, malic, tartaric, tricarballylic, and citric acids in aqueous solution has been investigated by means of IR and 13C NMR spectroscopy. The complex formation is reflected in the IR frequency shifts for the COO-stretching vibrations (yM(COO) and vs(COO)) and the asymmetric 0=U=0 stretching mode 03). The possible coordination structures of COO groups to the uranyl ion in the individual systems are discussed in terms of the IR frequencies of the vas(COO) and ys(CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
129
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(144 citation statements)
references
References 0 publications
14
129
1
Order By: Relevance
“…For the UO 2 (OAc) 3 Ϫ in an organic solvent (CH 2 Cl 2 ), the asym and sym values were similar to those in aqueous media, at 1548 and 1461 cm…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…For the UO 2 (OAc) 3 Ϫ in an organic solvent (CH 2 Cl 2 ), the asym and sym values were similar to those in aqueous media, at 1548 and 1461 cm…”
mentioning
confidence: 57%
“…Bidentate coordination is also seen in the IR spectra of crystalline uranyl acetate compounds: the asym and sym values for Na[UO 2 (OAc) 3 ] were 1537 and 1472 cm Ϫ1 (⌬ asym-sym value of 65 cm Ϫ1 ), [5] and in this salt the binding mode was confirmed by the crystal structure [6]. The interpretation of the IR spectrum of crystalline UO 2 (OAc) 2 )) [2].…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…In the solution phase, as mentioned above, based on the concentration analysis and potentiometric studies previously reported [15,23] the only uranyl species is the 2:2 binuclear uranyl malate complex. It is expected that the stability constants of most of the complex species change with temperature.…”
Section: Isotopic Equilibrium Constantmentioning
confidence: 82%
“…Unfortunately only n 3 , the U = O asymmetric stretching, has been measured. It was found to be 962.4 cm -1 in the case of the uranyl-aqua ion [23] and to decrease to 916.2 cm -1 in the case of U(VI) malate [17,23]. This reduction in the energy of n 3 , which is accompanied by bond elongation in case of the U(VI) malate species, is believed to be due to the stronger coordination of the U atom by the oxygen atoms of the malate ligand.…”
mentioning
confidence: 97%